Investigating the Impact of Economic Development, Energy Consumption, International Trade and Population on CO2 Emission of a Country: Evidence from an Emerging Economy - Lalon, Raad Mozib; Khan, Tasneema; Shaheen, Shagufta; Ul-Haq, Minhaz (International Journal of Energy Economics and Policy, 2023)
This paper investigates the consequences of economic development, along with energy consumption, international trade, and population growth, on the CO2 emissions of Bangladesh as a participant in an emerging economy, covering periods from 1972 to 2021. The unit root properties of the variables have been tested using the Augmented Dickey-Fuller (ADF) approach to examine the presence of stationary of data series. To check for co-integration in the data series of variables included in the models, we used the ARDL (Autoregressive Distributive Lag) bounds testing approach. In addition, the VECM (Vector Error Correction Model) Granger Causality approach has been used to examine the casual relationship between the selected variables representing the proxy for determinants of CO2 emission in Bangladesh. Our investigation confirms the co-integration between the data series, followed by the significant impact of these variables on CO2 emissions of Bangladesh. More precisely, GDP being the proxy of economic development, energy consumption, merchandise trade as a proxy for international trade, and population growths have had a significant positive impact on the CO2 emissions of Bangladesh since its inception.